Air quality simulation of NOX over the tropical coastal city Chennai in southern India with FLEXPART-WRF. (March 2016) - Madala, Srikanth; Hari Prasad, K.B.R.R.; Srinivas, C.V.; Satyanarayana, A.N.V.
Abstract: Chennai is a rapidly growing metropolitan coastal city in southern India with several major sources of pollution. The complex coastal meteorology influences the pollutant transport in different seasons. In this study, the air quality pattern in Chennai with respect of NOX over different seasons are simulated with FLEXPART-WRF Lagrangian Particle Dispersion Model (LPDM) considering release inventory of industrial, vehicular and domestic sources of pollution from seven different locations in Chennai. The meteorological fields for dispersion calculation are simulated using Advanced Research WRF (ARW) mesoscale model at a high resolution (3 km). Air quality data in the study region available at six different places are used for comparing model outputs over 12 days in each season (winter, pre-monsoon, monsoon and post-monsoon). The Hanna diffusion scheme in FLEXPART-WRF is modified with new seasonal empirical turbulent intensity relationships derived as a function of atmospheric stability from turbulence data. Simulated concentrations are evaluated by varying the diffusion schemes (Hanna, modified Hanna) in FLEXPART and the planetary boundary layer (PBL) schemes [YSU, ACM2 and MYNN2] in ARW. Simulations revealed distinct seasonal variation of dispersion patterns of NOX due to seasonal flow-field variation in the study region. It is found that, the new turbulence intensity relationships provide better comparisons for concentrations of NOX relative to the default Hanna relationship. Further, simulations using ACM2 PBL significantly reduced the negative bias and errors in concentration due to capturing the flow-field and other meteorological variables well. The study demonstrates the utility of FLEXPART for air quality modeling in the coastal city. Highlights: Air quality for NOX over Chennai in different seasons simulated with FLEXPART-WRF. Impact of different PBL physics in WRF studied on simulated concentrations. ACM2 well represented the flow field characteristics in various seasons. New turbulence intensity relationships incorporated in Hanna scheme in FLEXPART. Modified Hanna scheme considerably improved the simulation of NOx concentrations.